Tinjauan Perekonomian Indonesia Sebelum dan Saat Pandemi Covid-19 Menggunakan Google Mobility Index - Muhammad Alfaris Kurniawan (EXERO : Journal of Research in Business and Economics, 2022)
The COVID-19 pandemic has had a significant impact on various sectors of people's lives, including the economic sector. The government has also taken various policies to break the chain of the spread of this virus. However, the reduced mobility of the people actually has an impact on the weakening of the economy. For this reason, this study aims to determine changes in people's mobility patterns due to the COVID-19 pandemic, analyze the effect of population mobility on economic activity, and forecast regional economic conditions in the fourth quarter of 2021. Big data is data on the movement of people's smartphones provided by Google can provide information on population mobility before and during the COVID-19 pandemic. The analytical method used in this research is descriptive analysis using line and bar graphs, and regression analysis using mixed data sampling panel regression (Panel-MIDAS). The results of the analysis show that there has been a change in population mobility due to the COVID-19 pandemic and the policies implemented by the government. In addition, population mobility can be an indicator in nowcasting gross regional domestic product (GRDP) with an average error rate of only 6.57 percent. Population mobility in parks and workplaces has a positive and significant effect on GRDP. Forecasting results show that in general, the regional economy in the fourth quarter of 2021 will increase with the assumption that there will be no significant decline in mobility in December 2021.